2006
DOI: 10.1074/jbc.m601299200
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Calpains Promote Caspase-12 and JNK Activation during Endoplasmic Reticulum Stress-induced Apoptosis

Abstract: Ubiquitously expressed -and m-calpain proteases are implicated in development and apoptosis. They consist of 80-kDa catalytic subunits encoded by the capn1 and capn2 genes, respectively, and a common 28-kDa regulatory subunit encoded by the capn4 gene. The regulatory subunit is required to maintain the stability and activity of -and m-calpains. Accordingly, genetic disruption of capn4 in the mouse eliminated both ubiquitous calpain activities. In embryonic fibroblasts derived from these mice, calpain deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(155 citation statements)
references
References 54 publications
9
140
2
2
Order By: Relevance
“…57 Activated caspase-12 then cleaves and activates procaspase-9, which in turn activates the downstream caspase cascade, including caspase-3, DNA fragmentation, and cell death. 58 Our results also showed that protein and gene expressions of caspase-12, caspase-7, and cleaved caspase-7 were significantly elevated during steatohepatitis together with the increased number of apoptotic hepatocytes, whereas they were reduced markedly after changing the diet. Furthermore, although the proliferation of hepatocytes did not show a clear change in the MCDD group, the ratio of hepatocyte proliferation/apoptosis decreased significantly, whereas it increased markedly after changing the diet to CD, indicating that the apoptotic caspase-12 pathway may also inhibit hepatocyte proliferation in MCDD-induced steatohepatitis.…”
Section: Discussionsupporting
confidence: 58%
“…57 Activated caspase-12 then cleaves and activates procaspase-9, which in turn activates the downstream caspase cascade, including caspase-3, DNA fragmentation, and cell death. 58 Our results also showed that protein and gene expressions of caspase-12, caspase-7, and cleaved caspase-7 were significantly elevated during steatohepatitis together with the increased number of apoptotic hepatocytes, whereas they were reduced markedly after changing the diet. Furthermore, although the proliferation of hepatocytes did not show a clear change in the MCDD group, the ratio of hepatocyte proliferation/apoptosis decreased significantly, whereas it increased markedly after changing the diet to CD, indicating that the apoptotic caspase-12 pathway may also inhibit hepatocyte proliferation in MCDD-induced steatohepatitis.…”
Section: Discussionsupporting
confidence: 58%
“…The negative results represented in Figure 2c led us to analyze other possibilities for calpainmediated BAX activation. Two manuscripts have already described that calpains control JNK1 activation 20 and that AIF is released from mitochondria by JNK1-mediated activation. 7 Moreover, it has been demonstrated that JNK phosphorylation and activation of the BH3-only proteins, BIM and BAD, couple the stress-activated signaling pathway to the BAX-dependent cell death machinery.…”
Section: Resultsmentioning
confidence: 99%
“…The unfolded and misfolded proteins activate a self-protective mechanism to upregulate the expression of some ER resident chaperones, such as glucose regulated protein 78 (GRP78), giving the affected cells a chance to survive (Reddy et al 2003;Luo et al 2006). When the cells are exposed to prolonged or strong ER stress, however, the expression of some apoptosis promoters, such as growth arrest and DNA damage-inducible gene 153 (GADD153), increases (Benavides et al 2005;McCullough et al 2001), caspase-12 is activated and in turn activates caspase-9 and caspase-3 (Morishima et al 2002;Tan et al 2006), resulting in apoptotic cell death. Because ER stress is so crucial to cell survival or death, it has become an attractive research focus in recent years.…”
Section: Introductionmentioning
confidence: 99%